2005
DOI: 10.1103/physrevlett.94.136802
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Dependent Inelastic Tunneling in a Single Metallofullerene

Abstract: We have measured the elastic and inelastic tunneling properties of isolated Gd@C(82) molecules on Ag(001) using cryogenic scanning tunneling spectroscopy. We find that the dominant inelastic channel is spatially well localized to a particular region of the molecule. Ab initio pseudopotential density-functional theory calculations indicate that this channel arises from a vibrational cage mode. We further show that the observed inelastic tunneling localization is explained by strong localization in the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 25 publications
7
99
0
Order By: Relevance
“…67,68 F (2) (E) is Lorente and Perrson's generalization of TH theory that also includes the lowest (second-) order inelastic contributions to the conductance due to the interaction with phonons; this approach has been used to simulate STM-IETS topographic images of vibrational resonances. 34,59,60 In our calculations, the electronic couplings matrix elements V i (r 0 ) are computed by introducing a ghost atom centered at the desired tip position r 0 with a single 1s orbital using parameters taken from the 3-21G basis set for silver atoms. The atomic overlap integrals 〈r 0 |R〉 with the molecule's atomic basis functions |R〉 are calculated so that the overlap coupling to the i th molecular orbital is given by where c iR are the molecular orbital coefficients.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 F (2) (E) is Lorente and Perrson's generalization of TH theory that also includes the lowest (second-) order inelastic contributions to the conductance due to the interaction with phonons; this approach has been used to simulate STM-IETS topographic images of vibrational resonances. 34,59,60 In our calculations, the electronic couplings matrix elements V i (r 0 ) are computed by introducing a ghost atom centered at the desired tip position r 0 with a single 1s orbital using parameters taken from the 3-21G basis set for silver atoms. The atomic overlap integrals 〈r 0 |R〉 with the molecule's atomic basis functions |R〉 are calculated so that the overlap coupling to the i th molecular orbital is given by where c iR are the molecular orbital coefficients.…”
Section: Numerical Proceduresmentioning
confidence: 99%
“…These include charge transport through single-molecule break junctions, [13][14][15] chemisorption and binding configurations, 16,17 chemical reactions at interfaces, [18][19][20] current induced dynamics, [21][22][23][24][25] and single-molecule adsorbates in scanning tunneling microscopy (STM) where the inelastic current can be resolved both spatially and spectrally. [26][27][28][29][30][31][32][33][34][35] Inelastic effects in single molecules are particularly intriguing because they can be observed without the loss of information associated with ensemble averaging. 36 Local environmental factors, such as binding configurations and orientational dependencies can be explored.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the microscopic characteristics of electron-vibration coupling across the surface of a single diamondoid, we performed spatially resolved IETS across individual tetramantane molecules [19][20][21] . We find that the pronounced inelastic signals at ±356 mV only exist on certain parts of the molecules, and become negligibly small elsewhere.…”
mentioning
confidence: 99%
“…By studying these subtle changes of the vibrational energy using STM-IETS with a molecularfunctionalized tip, it has been demonstrated that STM-IETS can provide information on the inner structure of a molecule [4,5] similarly to atomic force microscopy (AFM) [6]. These advantages of STM-IETS have accelerated research in related fields [7][8][9][10][11][12][13][14][15][16]. Owing to recent progress in the theoretical description of IETS [17][18][19][20][21][22], the qualitative understanding has been improved considerably: the symmetry of the wave functions of a tip and a molecule on a substrate and a vibrational mode of the molecule are predicted to influence the efficiency of the inelastic process (γ inel ) for the tunneling current involving the molecule.…”
mentioning
confidence: 99%